Investment in Education as Development Human Resources at Madrasah Aliyah Negeri - Syifa Sayla Ramadhani; Annisa Silviani; Ainur Rahman; Hasyim Asy’ari; Zahruddin (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
The discussion in this study is about basic education in order to improve the quality of the Human Development Index. The importance of discussing these issues regarding aspects of education as one of the most important assets in order to achieve national development goals in a country. The purpose of this study is to find out how education is an investment in human resources in MA Negeri 1 Bekasi City. This research uses a qualitative descriptive approach. The research data was obtained from observation, interviews and documentation. The results of the discussion in this study are regarding the potential of human resources as educational investment capital or human capital in education at MA Negeri 1 Bekasi City. Investment in education at MAN 1 Bekasi City for the community in the field of education in the city of Bekasi is graduates who are accepted at advanced level education units in both public and private tertiary institutions. This improves the quality of life of educated graduates.